Death by black hole : and other cosmic quandaries - Tyson, Neil deGrasse (New York : W.W. Norton, 2007)
A collection of essays on the cosmos, written by an American Museum of Natural History astrophysicist, includes "Holy Wars," "Ends of the World," and "Hollywood Nights."
Section 5 : When the universe turns bad : all the ways the cosmos wants to kill us -- 28. Chaos in the solar system -- 29. Coming attractions -- 30. ends of the world -- 31. Galactic engines -- 32. Knock 'em dead -- 33. Death by black hole -- Section 6 : Science and culture : the ruffled interface between cosmic discovery and the public's reaction to it -- 34. Things people say -- 35. Fear of numbers -- 36. On being baffled -- 37. Footprints in the sands of science -- 38. Let there be dark -- 39. Hollywood nights -- Section 7 : Science and God : when ways of knowing collide -- 40. In the beginning -- 42. Holy wars -- 42. The perimeter of ignorance -- References -- Name index -- Subject index.
Includes bibliographical references (p. [343]-368) and indexes.
Keywords: Cosmology -- Popular works; Exobiology -- Popular works; Religion and science -- Popular works; Solar system -- Popular works